Robust Control of Elastic Drive Systems Using The Immersion and Invariance Methodology - Khan, Irfan Ullah (2013)
A Master of Science thesis in Mechatronics Engineering by Irfan Ullah Khan entitled, "Robust Control of Elastic Drive Systems Using The Immersion and Invariance Methodology," submitted in October 2013. Thesis advisor is Dr. Rached Dhaouadi. Available are both soft and hard copies of the thesis.